2023
DOI: 10.1186/s40066-023-00421-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting soil quality among smallholder macadamia farms in Malawi

Abstract: Declining soil fertility limits smallholder macadamia productivity in Malawi. To reverse this trend, it is essential to apply organic and inorganic fertilisers in an efficient and effective manner. Yet, fertilizer recommendations for smallholder macadamia (Macadamia integrifolia) production in Malawi are not site-specific. Nutrient imbalances can occur if fertilisers are applied without a clear understanding of whether they are required or not. This may lead to yield losses, unnecessary costs, and other enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Sod producers rely on inorganic fertilizers, particularly through foliar application, to enhance soil quality [9]. Research from the University of Michigan revealed that crops assimilate over 90% of nutrients from foliar-applied fertilizers and in sandy soil conditions, the effectiveness of foliar fertilizers is 20 times greater than soil application which soil conditions are not ideal.…”
Section: Conventionalmentioning
confidence: 99%
“…Sod producers rely on inorganic fertilizers, particularly through foliar application, to enhance soil quality [9]. Research from the University of Michigan revealed that crops assimilate over 90% of nutrients from foliar-applied fertilizers and in sandy soil conditions, the effectiveness of foliar fertilizers is 20 times greater than soil application which soil conditions are not ideal.…”
Section: Conventionalmentioning
confidence: 99%
“…Bananas and citrus are particularly important, constituting a staple part of the diet in rural and urban areas, with approximately 95% of their production consumed domestically [4,5]. Additionally, coffee and tea are major products consumed locally and exported [6,7].…”
Section: Introductionmentioning
confidence: 99%